The Economics of Abduction Marriage: Evidence from Ethiopia - Jorge Garcia-Hombrados; Lindsey Novak (Institute of Labor Economics (IZA), 2024)
A sizable share of marriages in several Asian and African countries are initiated by the man abducting the woman he wishes to wed. In this paper, we use quantitative and qualitative methods to characterize the practice of abduction marriage in Ethiopia. We first present the results from in-depth qualitative surveys with community leaders and abducted women in the Gambella region of Ethiopia to gain a deeper understanding of how the practice functions in these communities. These interviews suggest that abduction is typically used to overcome the refusal of the woman's family. Second, we use Demographic and Health Survey along with ethnographic data to characterize women and ethnic groups affected by this practice in Ethiopia. Finally, we empirically examine the central hypothesis about the persistence of this practice and find evidence consistent with the hypothesis that men often use abduction to improve bargaining power in marriage negotiations and reduce the size of the bride price payment. Specifically, we demonstrate that droughts - a proxy for income shocks in this setting - increase the probability of abduction marriage only for women from ethnic groups that traditionally exchange a bride price.
Keywords: D1; D7; I3; J1; O1; Z1; 330; abduction marriage; marriage markets; social norms; bride price